Asgarova, Gunel - (:unkn) unknown (My University, 2026)
Gunel Alasgarova Rovshan was born on July 28, 1997, in the city of Ismayilli, Azerbaijan. She completed her secondary education at Secondary School No. 14 in the Nasimi District of Baku, where she studied from 2003 to 2014. Between 2004 and 2009, she graduated from the Mstislav Rostropovich Music School in Baku, specializing in piano. From 2014 to 2018, she studied Design at the Faculty of Architecture of the Azerbaijan University of Architecture and Construction, graduating with a Bachelor's degree with honors. From 2018 to 2019, she worked as a designer at ITALDIZAYN OJSC. In 2019, she continued her professional career as a designer at the Baku branch of Aran Mobilya Dekorasyon İnşaat Sanayi ve Ticaret Limited Şirketi. Between 2020 and 2022, she worked as an independent design professional in the Russian Federation. From 2021 to 2023, she completed her Master's degree in Design and Technical Aesthetics at the Azerbaijan University of Architecture and Construction. Since 2023, she has been the founder and Director of BURO 7 LLC. In the same year, she joined the Azerbaijan University of Architecture and Construction as an Assistant Lecturer, where she continues her academic and teaching activities.